2013
DOI: 10.1038/cr.2013.95
|View full text |Cite
|
Sign up to set email alerts
|

An ABA-mimicking ligand that reduces water loss and promotes drought resistance in plants

Abstract: Abscisic acid (ABA) is the most important hormone for plants to resist drought and other abiotic stresses. ABA binds directly to the PYR/PYL family of ABA receptors, resulting in inhibition of type 2C phosphatases (PP2C) and activation of downstream ABA signaling. It is envisioned that intervention of ABA signaling by small molecules could help plants to overcome abiotic stresses such as drought, cold and soil salinity. However, chemical instability and rapid catabolism by plant enzymes limit the practical app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
182
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 176 publications
(184 citation statements)
references
References 27 publications
0
182
0
2
Order By: Relevance
“…The delayed wilting and drying in pRD29A::PYL9 transgenic plants was correlated with a reduction in water loss from the soil, indicating a reduction in transpiration. This result revealed that PYL9, when driven by the pRD29A promoter, is useful for generating transgenic plants that are extremely resistant to drought when treated with ABA or ABAmimicking compounds (26,27). We chose the pRD29A::PYL9 transgenic lines for additional study (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The delayed wilting and drying in pRD29A::PYL9 transgenic plants was correlated with a reduction in water loss from the soil, indicating a reduction in transpiration. This result revealed that PYL9, when driven by the pRD29A promoter, is useful for generating transgenic plants that are extremely resistant to drought when treated with ABA or ABAmimicking compounds (26,27). We chose the pRD29A::PYL9 transgenic lines for additional study (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Structural and biochemical studies also reveal several divergences among PYR/PYLs, particularly with respect to oligomeric structure and the perception of chemical agonists (Dupeux et al, 2011b;Hao et al, 2011;Okamoto et al, 2013). Activation of dimeric receptors by the ABA agonist quinabactin, which also activates to some extent PYL5 and PYL7, is enough to elicit both seed and vegetative responses to ABA (Cao et al, 2013;Okamoto et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…ABA binding stabilizes the RCAR-PP2C complex and releases PP2C downstream targets from the latent inhibition by the protein phosphatase (9,10); however, a few RCAR members are capable of regulating PP2Cs in the absence of ABA (11). ABA holo-receptors strongly discriminate against both nonphysiological ABA stereoisomers (8,12) and ABA biosynthetic precursors (13), but some receptor complexes tolerate binding of structurally unrelated ABA agonists (7,(14)(15)(16).…”
mentioning
confidence: 99%